Genome-wide characterization, phylogenetic and expression analysis of Galectin gene family in Golden pompano Trachinotus ovatus - Pan, Jin-Min; Liang, Yu; Zhu, Ke-Cheng; Guo, Hua-Yang; Liu, Bao-Suo; Zhang, Nan; Xian, Lin; Zhu, Teng-Fei; Zhang, Dian-Chang (Frontiers in Immunology, 2024)
Galectins (Gals) are a type of S-type lectin that are widespread and evolutionarily conserved among metazoans, and can act as pattern recognition receptors (PRRs) to recognize pathogen-associated molecular patterns (PAMPs). In this study, 10 Gals (ToGals) were identified in the Golden pompano (Trachinotus ovatus), and their conserved domains, motifs, and collinearity relationships were analyzed. The expression of ToGals was regulated following infection to Cryptocaryon irritans and Streptococcus agalactiae, indicating that ToGals participate in immune responses against microbial pathogens. Further analysis was conducted on one important member, Galectin-3, subcellular localization showing that ToGal-3 protein is expressed both in the nucleus and cytoplasm. Recombinant protein obtained through prokaryotic expression showed that rToGal-3 can agglutinate red blood cells of rabbit, carp and golden pompano and also agglutinate and kill Staphylococcus aureus, Bacillus subtilis, Vibrio vulnificus, S. agalactiae, Pseudomonas aeruginosa, and Aeromonas hydrophila.This study lays the foundation for further research on the immune roles of Gals in teleosts.